Carbohydrate Derived Fulvic Acid for the Treatment of Vulvovaginal Candidiasis - Stewart Clark; Michael Graz (Journal of Global Antimicrobial Resistance)
AIM: To evaluate the efficacy of carbohydrate derived fulvic acid (CHD-FA) against clinical isolates of Candida species causing vulvovaginal candidiasis (VVC). BACKGROUND: Therapeutic failure in the treatment of VVC is common and new, effective treatment options need to be developed. CHD-FA is a mixture of aliphatic and aromatic carboxylic acids that are produced by wet oxidation of sucrose. CHD-FA has previously been shown to exhibit microbiocidal activity against Candida albicans. This study aims to evaluate the antifungal activity of CHD-FA against clinical isolates associated with VVC and to investigate its effect on inflammatory markers. METHODS: MICs of CHD-FA were evaluated using the EUCAST method for MICs in fermentative yeasts against clinical isolates of C.albicans, C.glabrata, C.tropicalis, C.parapsilosis, C.krusei and C.auris provided by Public Health Wales. Furthermore, we evaluated how CHD-FA affected IL-6 and TNF-α in hPBMCs and THP-1 cells to identify anti-inflammatory effects using IL-6 and TNF-α ELISA kits. RESULTS: CHD-FA was highly active against all of the Candida species tested, including C.auris, with planktonic MIC's ranging from 0.1% for C.parapsilosis and C.auris to the highest of 0.55% for C.tropicalis. In a mammalian cell culture model and using freshly isolated white blood cells, CHD-FA was shown to significantly down-regulate key inflammatory mediators by between 77%-92% for IL-6 and 24-72% for TNF-α. CONCLUSIONS: CHD-FA was shown to possess effective antifungal activity, whilst also being able to down-regulate inflammation. This spectrum of function makes CHD-FA an attractive alternative in the treatment of VVC.